Modularizing honeycombs for enhancement of strength and energy absorption. (1st January 2022) - Li, Zhen; Sun, Huiming; Wang, Tao; Wang, Liangmo; Su, Xiaoping
Highlights: Multi-directional graded design concept is proposed and applied to honeycombs. It can double or more the strength of honeycombs. The enhancement of this graded design can be easily tailored by varying design parameters. The enhancement of strengthgives rise to dramatic improvement of energy absorption. Modularized design could be adaptive to many kinds of honeycomb structures. Abstract: Graded design is an advanced approach that is able to enhance mechanical properties of honeycombs while keeping their lightweight, but very few studies have extended graded design to high dimension and have studied effects of multiple graded designs on mechanical properties of honeycombs. This paper advances the state of the art and proposes a multi-directional graded design to improve strength and energy absorption of regular hexagonal honeycombs. Specifically, the honeycomb is partitioned into modules along y and z directions, and each module possesses its unique relative density. The design principle of density distribution is defined, and design rules between design parameters are analyzed and discussed. Theoretical and numerical models are created to investigate effects of multi-directional graded design on the mechanical properties. 3D printing prototypes made of AlSi10Mg are manufactured. Quasi-static compression tests are conducted, and utilized to validate both theoretical and numerical models. Investigations show that with the same weight, multi-directional graded design can double or more the strength and energy absorption ability of honeycombs compared with those of the corresponding uniform honeycombs. The enhancement coefficient is proportional to graded coefficient and modular number in either direction. However, it is insensitive to the average relative density of honeycombs, through which the design circle time could be reduced significantly in practice. In addition, the preliminary analyses of adaptivity show that multi-directional graded design is suitable for several honeycombs with different unit cells. This multi-directional graded design paves a way to design advanced honeycombs with lighter weight, higher strength and more excellent energy absorption ability.